Jumping the Queue: Nepotism and Public-Sector Pay - Andri Chassamboulli; Pedro Maia Gomes (Institute of Labor Economics (IZA), 2020)
We set up a model with search and matching frictions to understand the effects of employment and wage policies, as well as nepotism in hiring in the public sector, on unemployment and rent seeking. Conditional on inefficiently high public-sector wages, more nepotism in public-sector hiring lowers the unemployment rate because it limits the size of queues for public-sector jobs. Wage and employment policies impose an endogenous constraint on the number of workers the government can hire through connections.
Keywords: E24; J31; J45; J64; 330; public-sector employment; nepotism; public-sector wages; unemployment; queues